Evaluating the acute toxicity and hepatoprotective effect of PROTECFUL hard capsule on paracetamol-induced acute hepatitis in mice - Tung, Tran Thanh; Lam, La Que; Loan, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2025)
Drug-induced liver injury is characterized by liver damage due to pharmaceutical compounds, resulting in a wide range of liver disorders, from asymptomatic elevations in liver enzymes to full liver failure. It is a leading cause of acute liver failure in many countries. This study investigated the acute toxicity and evaluated hepatoprotective effects on paracetamol-induced acute hepatitis of PROTECFUL hard capsules in Swiss mice. The acute toxicity was assessed through oral administration, and a fifty percent lethal dose was determined using the Litchfield-Wilcoxon method. In the paracetamol-induced acute hepatitis model, mice were orally administered distilled water, silymarin at 140 mg/kg per day, or PROTECFUL hard capsules at 345.6 and 1036.8 mg/kg/day. All indexes, including biochemical indicators (AST, ALT), liver malondialdehyde, glutathione concentration, and microscopic liver images, were evaluated. Regarding acute toxicity, our findings showed that the maximum tolerated dose was 35.4 times higher than the expected human dose without symptoms of acute toxicity. PROTECFUL-treated groups at both doses tended to decrease liver weight and lower liver enzyme activity compared to the model group. The histopathological examination of the liver in the PROTECFUL-treated groups tended to reduce liver degeneration and inflammatory cell infiltration. In summary, these findings suggest that PROTECFUL shows no acute toxicity and tends to have a hepatoprotective effect against paracetamol-induced liver injury.